2020
DOI: 10.1108/bfj-07-2019-0575
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative study investigating food choices and perceived psychosocial influences on eating behaviours in secondary school students

Abstract: PurposeChildhood obesity is a major global health concern. Understanding children's and adolescent’s eating behaviours and promoting healthier behaviours is key for reducing the negative health outcomes associated with obesity. The current study explored the perceptions of healthy eating behaviours and the influences on eating behaviours amongst 11-to-13-year-old secondary school students.Design/methodology/approachNine semi-structured same-sex focus group discussions were conducted in schools located in depri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
42
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(48 citation statements)
references
References 32 publications
5
42
1
Order By: Relevance
“…Family modeling of healthy eating habits [35,37,43,44,47,[55][56][57]59,66,68,70,77,80] Encouragement and praise [35,38,44,49,51,66,68,69,71,75,77,80] Parental concern on adolescent's health [38,56,57,66,78] Adolescent acting as a role model in the family [77,78] Family modeling of unhealthy eating habits [39,40,[46][47][48][49][50]54,59,68,69,[72][73][74]79] Lack of parental concern on adolescent dietary issues (e.g., body weight is not important for the young) [42,…”
Section: Cultivation Of Preferencementioning
confidence: 99%
See 3 more Smart Citations
“…Family modeling of healthy eating habits [35,37,43,44,47,[55][56][57]59,66,68,70,77,80] Encouragement and praise [35,38,44,49,51,66,68,69,71,75,77,80] Parental concern on adolescent's health [38,56,57,66,78] Adolescent acting as a role model in the family [77,78] Family modeling of unhealthy eating habits [39,40,[46][47][48][49][50]54,59,68,69,[72][73][74]79] Lack of parental concern on adolescent dietary issues (e.g., body weight is not important for the young) [42,…”
Section: Cultivation Of Preferencementioning
confidence: 99%
“…Family norm and role modeling can be both facilitators of and barriers to healthy eating in adolescents. Aside from listening to their parents' advice, adolescents also choose their food by observing their parents' and siblings' eating habits of both healthy [35,37,43,44,47,[55][56][57]59,66,68,70,77,80] and unhealthy foods [39,40,[46][47][48][49][50]54,59,68,69,[72][73][74]79]. Parents who followed the same rules as they told their children enhanced the formation of the family norm [56,80].…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…A review of youth-targeted food marketing expenditures (Rummo et al, 2020) concluded that unhealthy food and beverages are highly followed by adolescents on social media platforms. In a study conducted on a sample of UK secondary school students (Calvert et al, 2020), the authors aimed to identify the factors that affect students' unhealthy eating habits. Although the surveyed students in the study were savvy of the consequences of eating unhealthy food, the authors indicated that environmental and social factors are the main deterrents for spreading healthy food consumption patterns among students.…”
Section: Introductionmentioning
confidence: 99%